IKOLI HARCOURT WHYTE, THE MAN AND HIS MUSIC: A CASE OF MUSICAL ACCULTURATION IN NIGERIA by Achinivu Kanu Achinivu, 2 vols. Beitrage zur Ethnomusikologie, No.7. Hamberg: Verlag der Musikalienhandlung, Karl Dieter Wagner, 1979. Vol. 1: 456 p., music; vol.2: 194 p., music, texts. - Erlmann, Veit (International Library of African Music, 1987)
pages: 165-167
Keywords: African Music; Nigeria; Musical Acculturation